Events as Platforms and Networks for Tourism Development in Moscow, Russia - Y. Alexandrova, Anna; V. Aigina, Ekaterina (Anais Brasileiros de Estudos Turísticos, 2022)
Events are used as strategic tools for tourism development in Moscow nowadays. They have thematic diversity and various scales. However, there is a need for a particular event strategy for active urban development, city image improvement, and tourism growth. The study focuses on Moscow 'event portfolio' and discusses events as platforms and networks for event growth and value creation. The research based on a case-study approach examines the evoluAtion of Moscow event tourism products and their conversion into a unique city platform appealing to both tourists and locals. Special attention is paid to Times and Epochs, the major historical re-enactment festival in Russia and one of the biggest in the world which started in 2011 and became very successful. The festival organizers have formed a comprehensive platform generating cultural events, media projects, and other activities to create new meaningful values based on direct communication and event involvement of the re-enactment community network, tourists and locals for further tourism development.